2009
DOI: 10.1517/13543780903329089
|View full text |Cite
|
Sign up to set email alerts
|

SR 57746A/xaliproden, a non-peptide neurotrophic compound: prospects and constraints for the treatment of nervous system diseases

Abstract: Neurodegenerative disorders such as Alzheimer's disease or amyotrophic lateral sclerosis as well as peripheral neuropathies are difficult to treat due to a limited range of effective drugs. Neurotrophic growth factors promote neuronal survival and differentiation and could hence be interesting tools to treat these diseases. Their therapeutic use is limited due their short half-life, their inability to cross the BBB and potential side effects including tumor promotion. SR 57746A is a non-peptide, orally active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Both affect serotonin 1A receptors, 30,31 and their trials may help resolve uncertainties regarding the role of this target in countering the effects of memory loss. Results from unsuccessful translation trajectories provide feedback on preclinical models or surrogate outcomes and validate pathophysiological theories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both affect serotonin 1A receptors, 30,31 and their trials may help resolve uncertainties regarding the role of this target in countering the effects of memory loss. Results from unsuccessful translation trajectories provide feedback on preclinical models or surrogate outcomes and validate pathophysiological theories.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, among the unsuccessful AD drugs are xaliproden and lecozotan. Both affect serotonin 1A receptors, and their trials may help resolve uncertainties regarding the role of this target in countering the effects of memory loss. However, none of the five xaliproden trials and only one of the eight lecozotan trials have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of TGF-β1 were increased by administering xaliproden to rats. Xaliproden is an agonist of the serotonin 5-HT 1A receptor, originally designed as a neuroprotective agent, but no longer in clinical trials [17]. Oral administration of xaliproden in rats causes an upregulation of circulating TGF-β1 levels by mechanisms that are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Because not all clinical trials involving central nervous disorders showed positive outcomes, the development of xaliproden as a novel drug in the treatment of these disorders was discontinued [17]. However, functional characterization of rats after oral treatment with xaliproden revealed that it markedly enhanced circulating levels of TGF-β1 by mechanisms that were only partly understood, and that plasma levels remained increased for as long as the compound was administered (Herbert, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…157 Other neurotrophic agents which have been investigated and have had positive results in preclinical animals include: prosaptide, 129 xaliproden, 276 retinoic acid, 277 and recombinant human glial growth factor 2 278 , but so far none have demonstrated appreciable efficacy in clinical trials. 279 Neurotrophic factors play an integral role not only in the survival of sensory neurons but also in the maintenance of the neurons, thus helping to establish the setpoints for neuronal sensitivity and growth. 280,281 Targeting this class of compounds, without a comprehensive understanding of how chemotherapy alters intracellular signaling pathways and the axonal transport mechanisms used to traffic the products of neurotrophin signaling, is proving to be very challenging.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%